La acción reflexiva en educación: buscando lo sustancial - Santos Rego, Miguel Anxo (Teoría de la Educación. Revista Interuniversitaria, 2009)
The first purpose of this study is to explore the main questions and topics connected with the recuperation of the «reflectivity» in education. Also, we pretend to inquiry into the most substantial aspects that accompany such recuperation in moments as live today, characterized by change and educational reform. Nowadays, the great emphasis in the notion of reflection has relation with the rise of qualitative research about the study of educational processes; without to forget the sharp load of situational and / or cultural factors in its treatment. Of course, this involve theoretical and methodological changes. On the other hand, we pay special attention to the process of reflection itself and some approaches post- Dewey. In the same way, we relate the topic with the professional education of teachers. Finally, the cognitive, critical, and narrative elements included in the process of reflection are traced and developed; considering a comprehensive framework of educational improvement for our time.